2003
DOI: 10.1554/03-094
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Hybrid Incompatibilities Between Drosophila Simulans and D. Mauritiana. Iii. Heterogeneous Accumulation of Hybrid Incompatibilities, Degree of Dominance, and Implications for Haldane's Rule

Abstract: The genetic basis of Haldane's rule was investigated through estimating the accumulation of hybrid incompatibilities between Drosophila simulans and D. mauritiana by means of introgression. The accumulation of hybrid male sterility (HMS) is at least 10 times greater than that of hybrid female sterility (HFS) or hybrid lethality (HL). The degree of dominance for HMS and HL in a pure D. simulans background is estimated as 0.23-0.29 and 0.33-0.39, respectively; that for HL in an F 1 background is unlikely to be v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
203
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(211 citation statements)
references
References 71 publications
7
203
1
Order By: Relevance
“…simulans stocks w; e (kindly provided by J Coyne) and simB (w; nt; III) were described in Tao et al, (2003). In the simB stock, the third chromosome is isogenic to the third chromosome of the highly inbred stock 13w 1 X 1 JJ (constructed by sib-pair mating for 20 generations from 13w- Liu et al, 1996).…”
Section: Drosophila Stocksmentioning
confidence: 99%
See 3 more Smart Citations
“…simulans stocks w; e (kindly provided by J Coyne) and simB (w; nt; III) were described in Tao et al, (2003). In the simB stock, the third chromosome is isogenic to the third chromosome of the highly inbred stock 13w 1 X 1 JJ (constructed by sib-pair mating for 20 generations from 13w- Liu et al, 1996).…”
Section: Drosophila Stocksmentioning
confidence: 99%
“…In the simB stock, the third chromosome is isogenic to the third chromosome of the highly inbred stock 13w 1 X 1 JJ (constructed by sib-pair mating for 20 generations from 13w- Liu et al, 1996). This chromosome does not carry a phenotypic marker, while the first and second chromosomes carry markers white (w) and net (nt), respectively (Tao et al, 2003). Drosophila mauritiana stocks (w; P [w+]) contain independent Pelement inserts on the third chromosome, which carry a functional copy of the gene white (True et al, 1996).…”
Section: Drosophila Stocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic studies in Drosophila demonstrated an excess of hybrid sterility loci on the X chromosome, a phenomenon referred to as Flarge X-effect_ (Orr & Coyne 1989, Tao et al 2003. Several X-linked hybrid sterility loci were also reported in mice (Oka et al 2004, Storchova et al 2004.…”
Section: Implications Of X-linked Meiosis Factorsmentioning
confidence: 99%